2011
DOI: 10.1002/anie.201104099
|View full text |Cite
|
Sign up to set email alerts
|

Foldamer‐Tuned Switching Kinetics and Metastability of [2]Rotaxanes

Abstract: Slip sliding away: foldamers can function as modular stoppers to regulate the slippage and de-slippage of pseudorotaxanes and the switching kinetics and metastability of bistable rotaxanes. By simply changing the solvent or the length of the hydrogen-bonded foldamer, the lifetime of the metastable co-conformation state can be increased dramatically, from several minutes to as long as several days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…Taking into account a rapid progress of supramolecular chemistry research, one should point out a growing attention paid today to foldamers. [134][135][136] They are helical receptors for rod-like guest molecules. It was found that double helical foldamers coiled around rod-shaped guest molecules can perform a screw-type motion, which does not occur in other molecular machines.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account a rapid progress of supramolecular chemistry research, one should point out a growing attention paid today to foldamers. [134][135][136] They are helical receptors for rod-like guest molecules. It was found that double helical foldamers coiled around rod-shaped guest molecules can perform a screw-type motion, which does not occur in other molecular machines.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 In rotaxanes 73a,b the foldamer-tuned switching of W between TTF and DNP stations was investigated. The TTF unit is more electron-rich than DNP, therefore the equilibrium is shifted toward W encircling the TTF station to form GSCC, and not toward W encircling DNP station to form the less stable MSCC.…”
Section: Scheme 19mentioning
confidence: 99%
“…16−18 We recently reported the preparation of tetrathiafulvalene/cyclobis(paraquat-p-phenylene) (TTF/ CBPQT 4+ )-based pseudo [2]rotaxanes T1−T3 (Scheme 1). 19,20 The ends of the threads are attached with a Frećhet-type G-3 dendron and a hydrogen-bonded arylamide foldamer, which is used to tune the threading/dethreading process of CBPQT 4+ . Structurally, these pseudo [2]rotaxanes are also reverse bolaamphiphiles with polar CBPQT 4+ being oriented in the middle of the systems and the hydrophobic dendron and arylamide located at the ends.…”
Section: ■ Introductionmentioning
confidence: 99%